2003
DOI: 10.1038/sj.bmt.1704329
|View full text |Cite|
|
Sign up to set email alerts
|

Defibrotide in the treatment of children with veno-occlusive disease (VOD): a retrospective multicentre study demonstrates therapeutic efficacy upon early intervention

Abstract: Summary:Veno-occlusive disease (VOD) of the liver is a complication observed particularly in patients undergoing hematopoietic stem cell transplantation (HSCT). Defibrotide (DF) is a polydeoxyribonucleotide with aptameric activity on endothelium. We evaluated in a retrospective analysis the efficacy of DF in pediatric patients developing hepatic VOD after HSCT. A total of 45 patients between 0.2 and 20 years (median age: 8.2 years) with hepatic VOD were treated with DF: 22 patients (49%) met risk criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
142
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 38 publications
7
142
1
6
Order By: Relevance
“…[24][25][26][27][28] In this population, neither heparin, nor ursodexosycholic acid administration appeared to minimize the risk of HVOD compared to that reported in other series. However, in the present series these drugs were not prospectively evaluated by randomization.…”
Section: Discussionmentioning
confidence: 68%
“…[24][25][26][27][28] In this population, neither heparin, nor ursodexosycholic acid administration appeared to minimize the risk of HVOD compared to that reported in other series. However, in the present series these drugs were not prospectively evaluated by randomization.…”
Section: Discussionmentioning
confidence: 68%
“…This finding is in keeping with previous reports suggesting that defibrotide can be administered with relative safety in this patient population. [8][9][10][11][12][13]17,18 Hyperbilirubinaemia was noted to be common in post allogeneic SCT in our series. Twenty-nine patients (50%) had a bilirubin X34 mmol/l although they failed to meet the Baltimore criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Early phase trials of defibrotide in the treatment of moderate to severe VOD have shown promising results with minimal attributable toxicity, encouraging complete response rates (36-50%) and consistent improvements in day þ 100 survival (at 30-60% versus 410% expected). [8][9][10][11][12][13] Several studies have investigated various types of VOD prophylaxis. The role of prophylactic anticoagulation remains uncertain despite a recent meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…6 Defibrotide, a single-stranded polydeoxyribonucleotide has anti-thrombotic, anti-inflammatory and anti-ischaemic properties and is recommended as the definitive treatment for VOD. [7][8][9][10] We report a single-centre experience based on case note review from over a 45-months period (January 2011 till September 2014) ( Table 1). A total of 273 allogeneic transplants were performed and VOD was diagnosed in 13.…”
mentioning
confidence: 99%
“…There is evidence that early treatment with defibrotide improves overall survival. 10 The criteria for diagnosing VOD have been defined more than two decades ago when myeloablative regimens were used for HSCT. Since then many new changes have occurred in the practice of transplantation with respect to conditioning intensity, alternative donors, other organs affected by VOD together with thrombocytopenia with rapid platelet consumption and rapid progression of VOD.…”
mentioning
confidence: 99%